2003
DOI: 10.1097/00000542-200311000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Reversal of Isoflurane Anesthesia in Rats as Measured by Cross-approximate Entropy of the Electroencephalogram

Abstract: C-ApEn of the bihemispheric electroencephalogram correlates with the return of spontaneous motor signs but not with the nociceptive reflex. Cerebral cholinergic activation dissociates central and peripheral anesthetic effects. C-ApEn, a novel measure of interhemispheric electroencephalogram independence, is a promising correlate of depth of sedation and state of consciousness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 44 publications
4
61
0
Order By: Relevance
“…Commensurate with our prior experience (Hudetz et al, 2003;Imas et al, 2005), and similar to that seen in dreamless sleep (Flint et al, 2010), 1.2% isoflurane produced lowfrequency, high-amplitude activity EEG (d-and h-dominated slow-wave activity) in our rats during the unstimulated state; this has been generally taken as a unitary indication of the unconscious state during which information flow in the brain is impeded (Alkire et al, 2008;Franks, 2008;Le Masson et al, 2002). At this isoflurane concentration, the righting reflex, a widely used behavioral surrogate index of consciousness in rodents (Franks, 2008), is absent.…”
Section: Discussionsupporting
confidence: 62%
“…Commensurate with our prior experience (Hudetz et al, 2003;Imas et al, 2005), and similar to that seen in dreamless sleep (Flint et al, 2010), 1.2% isoflurane produced lowfrequency, high-amplitude activity EEG (d-and h-dominated slow-wave activity) in our rats during the unstimulated state; this has been generally taken as a unitary indication of the unconscious state during which information flow in the brain is impeded (Alkire et al, 2008;Franks, 2008;Le Masson et al, 2002). At this isoflurane concentration, the righting reflex, a widely used behavioral surrogate index of consciousness in rodents (Franks, 2008), is absent.…”
Section: Discussionsupporting
confidence: 62%
“…The results are generally consistent with previous studies. Increasing central Ach levels is known to reduce the depth of anesthesia (Meuret et al, 2000;Hudetz et al, 2003). Laalou et al (2008) reported that NBM lesion with 192IgG-saporin increased the anesthetic, but not the subanesthetic, effects of cumulative doses of propofol (i.p.).…”
Section: Correlation Of Averagementioning
confidence: 99%
“…An anticholinesterase that increased central Ach levels was shown to reduce the depth of anesthesia induced by propofol or isoflurane (Meuret et al, 2000;Hudetz et al, 2003). Pain et al (2000) reported that central Ach depletion by intracerebroventricular (icv) administration of 192IgG-saporin reduced the sedative potency of low-dose (30 mg/kg i.p.)…”
Section: Introductionmentioning
confidence: 99%
“…The effect of anesthetics on AChE activity is poorly documented (Mazzanti et al, 1986;Lintern et al, 2000). Although a relationship between Ach activity and anesthesia has emerged (Hudetz et al, 2003;Leung et al, 2011), to our knowledge the effects of anesthetic products on the cholinergic system of fish are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%